Artificial neural network with radial basis function in model predictive control of chemical reactor - Samek, David; Dostal, Peter (Wydawnictwa AGH, 2009)
This paper describes the application of artificial neural network with radial basis function as a predictor in model predictive control. Radial basis function neural networks are known for their fast training. Thus, this type of artificial neural networks offers promising way how to reduce computational cost during offline predictor training and eventual online adaptation. The features of this type of artificial neural network are presented in simulations in MATLAB/Simulink on the nonlinear system control. The aim of this paper is to suggest one approach how to solve nonlinear prediction problem using artificial neural network respecting computational demands of the predictor.

Artykuł jest poświęcony zastosowaniu sztucznych sieci neuronowych z radialnymi funkcjami bazowymi jako predykatora w modelach sterowania predyktywnego. Sieci radialne są znane z możliwości ich szybkiego uczenia. Dlatego ten typ sztucznych sieci neuronowych umożliwia redukcję czasu obliczeń podczas uczenia sieci w trybie off-line i ewentualnych zastosowań on-line. Cechy omawianych aplikacji sieci neuronowych przedstawiono w symulacyjnych obliczeniach sterowania nieliniowego układu z wykorzystaniem środowiska MATLAB/Simulink.
Sztuczne sieci neuronowe z radialnymi funkcjami bazowymi w predyktywnym sterowaniu reaktorem chemicznym
Mechanics
References s. [95].
Keywords: Artificial Neural Networks; radial basis function; model predictive control; sztuczne sieci neuronowe; radialne funkcje bazowe; sterowanie predykcyjne